DM‐induced Hypermethylation of IR and IGF1R attenuates mast cell activation and airway responsiveness in rats. Issue 24 (3rd November 2020) - Fu, Dan; Zhao, Hailu; He, Liang; Feng, Huafeng
Abstract: Diabetes has been reported to modulate the airway smooth muscle reactivity and lead to attenuation of allergic inflammatory response in the lungs. In this study, we aimed to study the effect of insulin on cell activation and airway responsiveness in patients with diabetes mellitus (DM). The airway contraction in rat model groups including a non‐DM group, a non‐DM+INDUCTION group, a DM+INDUCTION group and a DM+INDUCTION+INSULIN group was measured to observe the effect of insulin on airway responsiveness. Radioenzymatic assay was conducted to measure the levels of histamine, and ELISA assay was conducted to measure bronchial levels of interleukin (IL)‐1b, tumour necrosis factor (TNF)‐a, cytokine‐induced neutrophil chemoattractant (CINC)‐1, P‐selectin and β‐hexosaminidase. The tension in the main and intrapulmonary bronchi of DM+INDUCTION rats was lower than that of the non‐DM+INDUCTION rats, whereas the treatment of insulin partly restored the normal airway responsiveness to OA in DM rats. The release of histamine was remarkably suppressed in DM+INDUCTION rats but was recovered by the insulin treatment. Also, OA significantly increased the levels of IL‐1b, TNF‐a, CINC‐1 and P‐selectin in non‐DM rats, whereas insulin treatment in DM+INDUCTION rats partly restored the normal levels of IL‐1b, TNF‐a, CINC‐1 and P‐selectin in DM rats. Moreover, the expression of IR and IGF1R was evidently suppressed in DM rats, with the methylation of both IR and IGF1R promoters was aggravated in DM rats. Therefore, we demonstrated that DM‐induced hypermethylation inhibited mast cell activation and airway responsiveness, which could be reversed by insulin treatment.